Two‐dimensional structure of long‐period pulsations at polar latitudes in Antarctica - Yagova, N. V.; Pilipenko, V. A.; Lanzerotti, L. J.; Engebretson, M. J.; Rodger, A. S.; Lepidi, S.; Papitashvili, V. O. (Journal of Geophysical Research, 2004)
Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/95097/1/jgra17193.pdf